2010
DOI: 10.1177/0957154x09102800
|View full text |Cite
|
Sign up to set email alerts
|

From psyche to soma? Changing accounts of antisocial personality disorders in the American Journal of Psychiatry

Abstract: The history of psychiatry is often portrayed through the metaphor of a pendulum, the profession swinging back and forth between a concern with psyche and soma. Recent work critiquing the pendulum metaphor, however, suggests that it does not account for the complexity of psychiatry. This article explores the metaphor through an analysis of the changing aetiological accounts of personality disorders associated with antisocial behaviour advanced in the American Journal of Psychiatry from 1950 onwards. It is argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 88 publications
0
28
0
Order By: Relevance
“…Critical of the use of the term psychopathy, Wootton wryly observed that one definition of the disorder given by the Royal Medico-Psychological Association (the forerunner of the Royal College of Psychiatrists) essentially reduced to the following statement: “psychopaths are extremely selfish persons and nobody knows what makes them so” (Wootton 1959, 249). Resonating with US debates about psychopathy (Pickersgill 2010), Wootton's doubts about the legitimacy of the concept were closely related to its ambiguity. As she noted: “The volume of the literature on the subject of psychopaths is rivaled only by the depth of confusion in which this literature is steeped” (Wootton 1959, 250).…”
Section: British Psychopathsmentioning
confidence: 99%
“…Critical of the use of the term psychopathy, Wootton wryly observed that one definition of the disorder given by the Royal Medico-Psychological Association (the forerunner of the Royal College of Psychiatrists) essentially reduced to the following statement: “psychopaths are extremely selfish persons and nobody knows what makes them so” (Wootton 1959, 249). Resonating with US debates about psychopathy (Pickersgill 2010), Wootton's doubts about the legitimacy of the concept were closely related to its ambiguity. As she noted: “The volume of the literature on the subject of psychopaths is rivaled only by the depth of confusion in which this literature is steeped” (Wootton 1959, 250).…”
Section: British Psychopathsmentioning
confidence: 99%
“…Of course, issues of ontological uncertainty are not unique to ASPD, or even to psychiatry. These have long been debated by clinicians internationally 26. However, when pertaining to forensic mental health, the ethical corollaries of uncertainty are significant to say the least.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, clinical experiments like NT seem to have two parallel objectives: neurophysiological malfunctions of the brain and the addict as the person. Such a duality and the related problems of multifactorial disorders are also characteristic of other fields of current psychiatry (see Helén, 2007;2011b;Pickersgill, 2010). In NT, the doubling of the object of the experiment points out a significant aspect of the translation of neurosciences in clinical practice.…”
Section: Unitary Addictionmentioning
confidence: 99%
“…Despite the progress of research in neurosciences, clinical reasoning and treatment practices are not directed by any model of explanatory synthesis. Instead, many theoretical approaches contribute to the discussion side by side, and the impact of neurosciences is unclear and restricted (Helén, 2011b;Pickersgill, 2010). Nevertheless, great expectations are attached to research of neurobiology of depression, anxiety, and various addictions by scientists, clinicians, policymakers, and lay public.…”
mentioning
confidence: 99%